Aqueous primer composition, laminate for packaging material, and method for producing laminate for packaging material
By using an aqueous primer composition optimized by surface tension and surface free energy and performing active energy ray curing thereon, the problem of insufficient transferability and leveling of the aqueous primer on paper substrate and ink layer in the prior art is solved, and efficient printing appearance uniformity and wipe resistance are achieved.
Patent Information
- Application Number
- CN202411541888.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-27
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-10-31
AI Technical Summary
In the prior art, the transferability and leveling of the aqueous primer on the paper substrate and the ink layer are insufficient, and the transfer and leveling of the active energy ray curing composition to the aqueous primer layer is poor, resulting in uneven gloss and uneven printing appearance.
An aqueous primer composition containing a binder resin, a body pigment and an aqueous solvent is used, and the surface tension of the composition is 24-38 mN/m and the surface free energy of the primer layer is 24-40 dyne/cm. These parameters are adjusted to optimize the performance of the primer layer, and the active energy ray curing composition is printed thereon.
Excellent transferability and leveling of the aqueous primer composition on the paper substrate and the ink layer are achieved, and after the active energy ray curing, good spot resistance and extinction resistance are obtained, significantly improving the uniformity of the printing appearance and wipe resistance.
Smart Images

Figure BDA0005112981300000261 
Figure BDA0005112981300000271 
Figure BDA0005112981300000291
Abstract
Description
Technical Field
[0001] The present invention relates to a water-based primer composition, a laminate for packaging materials, and a method for producing the laminate for packaging materials.
[0002] More specifically, the present invention relates to an aqueous primer composition for forming a primer layer of a packaging laminate having a paper substrate, a primer layer and an active energy ray-curable layer in this order, the packaging laminate, and a method for producing the packaging laminate. Background Art
[0003] In recent years, in the field of packaging using paper substrates (also called paper objects), for the purpose of giving durability and beauty to printed materials, research on applying top coating varnish to the printed materials after printing color inks on various substrates has been widely carried out. Regarding paper packaging, when displayed in a store after printing, glossiness is sometimes required, and matteness is sometimes required for beauty. In recent years, in particular, the demand for printed materials with matte effects has increased. In addition, in the field of paper packaging, top coating varnish is particularly used for packaging of high-end cosmetics, etc. The appearance (beautification) quality of the printed material affects the purchasing desire of customers due to the expression of high-end feeling, so it is extremely important to guarantee its quality. It should be noted that in addition to top coating varnish, there are also marks such as overprint (OP) varnish, but they are used synonymously with top coating varnish.
[0004] In addition, the function of the top coat varnish is not only required to provide the printed material with gloss and matte appearance, but also to provide durability for protecting the printed pattern. Therefore, active energy ray-curable coating liquids with excellent film strength are widely used.
[0005] As a top coating varnish with a matte effect, various particles are added to the coating solution in most cases. The top coating varnish forms a concavoconvex by particles present on the surface of the dried or cured coating film, and light diffuses and reflects at the interface, thereby giving a matte feel. On the other hand, in the case where the substrate is a paper substrate, due to the solvent, low molecular weight component, resin component, etc. in the top coating varnish, the substrate can be infiltrated, or the transfer and leveling during printing are poor, thus forming a large number of particles in the pattern and the position where there is not much, thus there is a problem of uneven gloss value and uneven (color spot) of printed appearance.
[0006] For the above-mentioned problems, in order to suppress the top coating varnish from penetrating into the paper substrate, a primer layer is usually provided under the top coating. For primers, in particular, from the perspective of reducing the load on the working environment and strengthening the chemical substance management restrictions of various countries in recent years and protecting the earth's environment, the requirements for water-based primers (water-based primers) are still high, rather than oil-based types using organic solvents. It should be noted that in addition to primers, there are also anchor varnishes (anchor varnish) and caulking varnishes, which are used synonymously with primers.
[0007] Patent Document 1 proposes a laminated body obtained by applying an aqueous anchor varnish containing a styrene-butadiene rubber emulsion having a glass transition temperature of 5° C. onto an aqueous printing ink layer printed on a paper substrate, and then applying an active energy ray-curable overprint varnish.
[0008] In addition, Patent Document 2 proposes a method of laminating a surface protective layer after laminating a full-surface coloring layer and a primer layer composed of a two-component curable urethane resin composed of acrylic polyol and isocyanate in this order on a fibrous substrate. However, in Patent Documents 1 and 2, there are still problems with the transfer and leveling properties of the water-based primer on the ink layer, and the transfer, leveling, and matte properties (matte feeling) of the active energy ray-curable composition to the water-based primer layer.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2007-45962
[0012] Patent Document 2: Japanese Patent Application Publication No. 2005-89932 Summary of the invention
[0013] Problems to be solved by the invention
[0014] An object of the present invention is to provide an aqueous primer composition having excellent transferability and leveling properties to a paper substrate and an ink layer, which has excellent color spot resistance (gloss unevenness resistance) when an active energy ray-curable composition is applied on the aqueous primer layer, and provides a laminate for packaging materials having excellent cosmetic appearance (matte properties).
[0015] Methods for solving problems
[0016] The embodiments of the present invention include the following contents. However, the present invention is not limited to the following embodiments but includes various implementation embodiments.
[0017] <1> A water-based primer composition is a water-based primer composition for forming a primer layer of a laminate for packaging materials having a paper substrate, a primer layer and an active energy ray-curable layer in this order, and contains a binder resin, an extender pigment and an aqueous solvent.
[0018] <2> As mentioned above <1> The surface tension of the water-based primer composition is 24-38 mN / m.
[0019] <3> As mentioned above <1> or <2> The water-based primer composition, wherein the surface free energy of the primer layer is 24 to 40 dyne / cm.
[0020] <4> As mentioned above <1> ~ <3> In any one of the water-based primer compositions, the aqueous solvent contains a hydrophilic organic solvent.
[0021] <5> As mentioned above <1> ~ <4> The water-based primer composition according to any one of the preceding claims, wherein the viscosity of the water-based primer composition is 50 to 2500 mPa·s.
[0022] <6> As mentioned above <1> ~ <5> The water-based primer composition described in any one of the above, wherein the binder resin comprises at least one selected from the group consisting of a water-based acrylic resin (A), a water-based urethane resin (B) and a water-based polyester resin (C).
[0023] <7> As mentioned above <1> ~ <6> The water-based primer composition described in any one of the above items, wherein the extender pigment comprises at least one selected from the group consisting of silicon dioxide, calcium carbonate, barium sulfate and talc.
[0024] <8> As mentioned above <1> ~ <7> The water-based primer composition described in any one of the above items, wherein the average particle size of the extender pigment is 1 to 10 μm.
[0025] <9> As mentioned above <4> ~ <8> In any one of the water-based primer compositions, the boiling point of the hydrophilic organic solvent is 70 to 90°C.
[0026] <10> As mentioned above <1> ~ <9> The aqueous primer composition described in any one of the above items is used for flexographic printing or gravure printing.
[0027] <11> A laminate for packaging material comprises a paper substrate, a primer layer formed from the above-mentioned aqueous primer composition, and an active energy ray-curable layer in this order, wherein the active energy ray-curable layer contains resin fine particles.
[0028] <12> As mentioned above <11> The laminate for packaging material further comprises an offset printing layer.
[0029] <13> As mentioned above <11> or <12> In the laminate for packaging material, the active energy ray-cured layer has a 60° specular glossiness of 40 or less.
[0030] <14> A method for producing a laminate for packaging materials, which is a method for producing a laminate for packaging materials having a paper substrate, a primer layer and an active energy ray-curable layer in sequence, comprising the steps of flexographically printing or gravure-printing an aqueous primer composition containing a binder resin, an extender pigment and an aqueous solvent on a paper substrate to form the primer layer, and irradiating the primer layer with active energy rays after printing an active energy ray-curable composition to form the active energy ray-curable layer.
[0031] Effects of the Invention
[0032] According to the present invention, a water-based primer composition and a laminate for packaging materials having excellent cosmetic appearance (matte property) and abrasion resistance are provided. The water-based primer composition is a water-based primer composition having excellent transferability and leveling properties to a paper substrate and an ink layer, and has excellent color spot resistance (gloss unevenness resistance) when an active energy ray-curable composition is applied on the water-based primer layer. DETAILED DESCRIPTION
[0033] Embodiments of the present invention will be described in detail below. The description of the constituent elements described below is an example (representative example) of the embodiments of the present invention, and the present invention is not limited to these contents unless it exceeds the gist of the present invention.
[0034] In this specification, "water-based primer composition" is sometimes referred to as "primer composition", but they are synonymous. "Laminate for packaging material" is sometimes referred to as "laminate", but they are synonymous. In addition, in the specification, "mN / m" is used as the unit of surface tension of liquid such as primer composition, and "dyne / cm" is used as the unit of surface tension of solid such as primer layer, that is, surface free energy. Different units but the same value, for example, when comparing the surface energy of primer layer with the surface tension of active energy ray curing composition, the values can be directly compared.
[0035] Hereinafter, the present invention will be described in detail.
[0036] <Water-based primer composition>
[0037] The present invention relates to a water-based primer composition, which is a water-based primer composition for forming the primer layer of a laminated body for packaging materials having a paper substrate, a primer layer and an active energy ray-cured layer in sequence, and the water-based primer composition comprises a binder resin, a body pigment and an aqueous solvent. The water-based primer composition is preferably used on a paper substrate and / or an ink layer formed arbitrarily on a paper substrate, and is preferably used as a primer layer of an active energy ray-cured layer. By containing a body pigment in the water-based primer composition, the penetration of the active energy ray-cured composition forming the active energy ray-cured layer into the paper substrate can be suppressed, and the inking and leveling of the active energy ray-cured layer are stable, so it is not easy to produce uneven gloss (color spots), and a uniform and high-grade appearance (matte feeling) can be obtained. If the surface tension of the water-based primer composition is 24 to 38 mN / m, it is easier to obtain the above effect, so it is preferred. However, the above-mentioned function is found based on investigation and is not particularly limited to the invention of this application.
[0038] (Surface tension of waterborne primer composition)
[0039] In the present invention, the surface tension of the aqueous primer composition is preferably 24 to 38 mN / m, more preferably 26 to 36 mN / m, and further preferably 27 to 33 mN / m. If it is 24 mN / m or more, the surface free energy of the primer layer is prevented from decreasing, and the transfer, ink adhesion, and leveling properties of the active energy ray-curable composition on the primer layer are improved. If it is 38 mN / m or less, the wettability to the paper substrate and the ink layer can be improved, and shrinkage craters can be suppressed.
[0040] As a method for making the surface tension of the water-based primer composition the above-mentioned range, the method for adjusting the type and addition of the extender pigment can be cited, and for example, the extender pigment can be used in the preferred manner described later. In addition, if a hydrophilic organic solvent is added, the surface tension tends to be reduced, and the hydrophilic organic solvent is preferably used in the preferred manner described later. In addition, additives such as surface conditioners can also be used to adjust, and if a surface conditioner is added, the surface tension tends to be reduced. It is possible to appropriately select from these methods and adjust to a specified range.
[0041] In the case of using only additives to adjust the surface tension of the water-based primer composition, the additives remain in the primer layer formed by printing and drying the composition, and the surface free energy of the primer layer is reduced, so when the active energy ray curing composition is printed on the primer layer, it is easy to become poor leveling. Therefore, by using a hydrophilic organic solvent in the water-based primer composition, there is an effect of reducing the surface tension of the water-based primer composition, on the other hand, it evaporates after drying and does not remain in the primer layer, and the surface free energy of the primer layer is not reduced. Therefore, it is easy to take into account the leveling of the water-based primer composition on the paper substrate and the ink layer and the leveling of the active energy ray curing composition on the primer layer, so it is more preferred. The above-mentioned function is found based on investigation and is not particularly limited to the present invention.
[0042] (Measurement method of surface tension)
[0043] The surface tension can be measured using, for example, a high-precision surface tension meter DY-700 (manufactured by Kyowa Interface Chemical Co., Ltd.) In the present invention, the liquid temperature during the measurement is set to 25°C.
[0044] <Primer layer>
[0045] The primer layer of the present invention is formed by an aqueous primer composition. The surface energy of the primer layer is preferably 24 to 40 dyne / cm, more preferably 26 to 38 dyne / cm, and further preferably 30 to 38 dyne / cm. If it is within the above range, the surface energy of the primer layer is lower than the surface tension of the active energy ray-curing composition, and the active energy ray-curing composition has good wetting and expansion on the primer layer. If it is above 24 dyne / cm, the transfer, inking, and leveling properties of the active energy ray-curing composition to the aqueous primer layer become good. If it is below 40 dyne / cm, the surface tension of the primer composition decreases in a linked manner, so a good matte feel can be obtained by suppressing the shrinkage cavities on the substrate and the ink layer.
[0046] As a method for making the surface free energy of the primer layer to be within the above-mentioned range, the method for adjusting the type and addition of the extender pigment can be cited, and can be used in the preferred mode described later. In addition, if the addition of the extender pigment increases, the surface free energy tends to rise, and if the particle size of the extender pigment decreases, the surface free energy tends to rise. In addition, the method for selecting the type of binder resin, the method for adjusting with additives such as surface conditioners, etc., can be appropriately selected from these methods and adjusted to the specified range.
[0047] In order to make the surface free energy of the primer layer within the above range, as a binder resin, it is preferred to contain at least one selected from the group consisting of an aqueous acrylic resin (A), an aqueous urethane resin (B) and an aqueous polyester resin (C), wherein the aqueous acrylic resin (A) is suitable and can be used in combination with two or more resins within the range that does not damage the effect of the present invention. By using the above-mentioned binder resin, it is easy to achieve a balance between the surface free energy of the primer layer and the surface tension of the active energy ray-cured composition, and the transfer, inking and leveling properties of the active energy ray-cured composition to the primer layer become good. The mass ratio of the binder resin in the aqueous primer composition is preferably 10 to 50% by mass, more preferably 20 to 40% by mass. The mass ratio of the binder resin in the primer layer is preferably 60 to 95% by mass, more preferably 70 to 85% by mass.
[0048] (Measurement method of surface free energy)
[0049] Here, the surface free energy is defined as "the free energy per unit area of the surface", which is the energy that the surface of the primer layer has in excess compared to the inside of the layer (main body). The larger the surface free energy of a solid, the easier it is for a gas or particle to be adsorbed, the easier it is for a liquid to be wetted, and the easier it is to adhere to other solids. The surface free energy can be measured by using a contact angle meter, etc., by analyzing the contact angle of water and hexadecane using the Kaelble-Uy method. In the present invention, the surface free energy of the primer layer is a value calculated by the following method using a fully automatic contact angle meter DM-701 manufactured by Kyowa Interface Science Co., Ltd. First, 1 μL of water (pure water) is dripped onto the surface of the primer layer, and the contact angle is measured after 30 seconds, and then the contact angle is measured in the same manner using n-hexadecane instead of water. Using the obtained contact angles of water and n-hexadecane, the surface free energy is calculated by the Kaelble-Uy method.
[0050] <Binder Resin>
[0051] The binder resin may be a known resin, and from the viewpoints of the substrate adhesion of the primer layer, the film strength, etc., it is preferably at least one selected from the group consisting of a water-based acrylic resin (A), a water-based urethane resin (B), and a water-based polyester resin (C), wherein a water-based acrylic resin (A) is preferred. In addition, two or more resins may be used in combination within the scope of not impairing the effects of the present invention.
[0052] The mass ratio of the binder resin in the water-based primer composition is 10 to 50 mass %, and more preferably 20 to 40 mass %. Within the above range, matte properties and scratch resistance become good.
[0053] (Water-based acrylic resin (A))
[0054] The aqueous acrylic resin (A) is a general term for aqueous acrylic emulsions (A1) and water-soluble acrylic resins (A2) (except for resins having urethane bonds). The aqueous acrylic resin (A) is a resin containing (meth)acrylate units, and examples thereof include polymers or copolymers of acrylic monomers such as (meth)acrylate alkyl esters, (meth)acrylic acid, (meth)acrylamide, and copolymers of the above acrylic monomers with monomers such as styrene and maleic anhydride. It should be noted that the acrylic monomer may have functional groups such as hydroxyl, carboxyl, and glycidyl. As the acrylic monomer, preferably, acrylates and methacrylates can be mentioned. For example, as acrylates, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, glycidyl acrylate, etc. can be exemplified; as methacrylates, preferably, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, etc. can be exemplified. In addition, carboxylic acid-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, or anhydrides and half esters thereof can also be used.
[0055] Among them, the acrylic monomer preferably includes methyl acrylate, ethyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylic acid, methacrylic acid, maleic acid, itaconic acid. In addition, as the styrene monomer constituting the styrene-acrylic resin, styrene, α-methylstyrene, β-methylstyrene, etc. can be exemplified. Among them, the styrene monomer preferably includes α-methylstyrene.
[0056] The mass ratio of the aqueous acrylic resin (A) in the binder resin is preferably 60 to 100 mass%, more preferably 80 to 100 mass%, particularly preferably 90 to 100 mass%. When it is within the above range, adhesion and scratch resistance become good.
[0057] (Water-based acrylic emulsion (A1))
[0058] The aqueous acrylic emulsion (A1) comprises at least one selected from styrene-acrylic emulsion resin and acrylic emulsion resin (wherein styrene-acrylic emulsion resin is excluded). Among them, preferably styrene-acrylic emulsion resin is included. The acrylic monomer constituting the acrylic resin can preferably use the same monomer as described above. It should be noted that the emulsion refers to a form in which the resin itself is insoluble or poorly soluble in water, but the resin is dispersed into small particles and stabilized. In addition, a copolymer emulsion obtained by copolymerizing the above-mentioned monomers by using a water-soluble acrylic resin as a polymer emulsifier can also be preferably used.
[0059] The average particle size of the aqueous acrylic emulsion (A1) is preferably 10 to 500 nm, more preferably 20 to 300 nm, and further preferably 30 to 250 nm. The average particle size can be measured, for example, as the value of D50 based on the dynamic light scattering method. In addition, the weight average molecular weight of the aqueous acrylic emulsion (A1) is preferably 2000 to 2000000, more preferably 5000 to 1500000, and further preferably 10000 to 100000. This is because, by being in the above range, the cohesive force of the coating film is improved and the abrasion resistance is improved. As the above-mentioned styrene-acrylic resin, for example, Joncryl PDX-7734 (Tg 40°C, solid content 41.4% by mass), Joncryl PDX-7538 (Tg 75°C, solid content 45.5% by mass) manufactured by BASF can be used. In addition, as an acrylic resin, Joncryl 60J, 70J, HPD-196, etc. manufactured by BASF can be used.
[0060] (Water-soluble acrylic resin (A2))
[0061] The water-soluble acrylic resin (A2) is preferably at least one selected from styrene-acrylic resin and acrylic resin (wherein, styrene-acrylic resin is excluded), which has a hydrophilic group such as a carboxyl group. In addition, it is preferably a water-soluble resin in which the hydrophilic group is solubilized by a basic compound. As the basic compound, preferably amine compounds, alkali metals, etc. can be mentioned. Specifically, as the above-mentioned amine compound, alkylamines such as ammonia, diethylamine, triethylamine, and ethylenediamine, and alkanolamines such as monoethanolamine, ethylethanolamine, diethylethanolamine, diethanolamine, and triethanolamine can be mentioned. As the above-mentioned alkali metal, sodium hydroxide, potassium hydroxide, etc. can be mentioned.
[0062] The acid value of the water-soluble acrylic resin (A2) is preferably 150 to 300 mgKOH / g, and more preferably 180 to 260 mgKOH / g. By being in the above range, the dispersion stability of the body pigment is improved, the leveling property during transfer is good, and the color spot resistance becomes good. The weight average molecular weight of the water-soluble acrylic resin (A2) is preferably 1500 to 60000, and more preferably 4000 to 30000. By being in the above range, the dispersion stability of the body pigment is improved, the leveling property during transfer is good, and the color spot resistance becomes good. As the water-soluble acrylic resin (A2), for example, AQURYS TYS-85, TYS-3000, LH52 manufactured by Gifu Shellac Manufacturing, Joncryl 60J, 70J, HPD-196, HPD-96J manufactured by BASF, etc. can be used.
[0063] In the water-based primer composition of the present invention, the water-based acrylic resin (A) contains at least one selected from the group consisting of a water-based acrylic emulsion (A1) and a water-soluble acrylic resin (A2). In some embodiments, the water-based acrylic resin (A) preferably contains a water-based acrylic emulsion (A1), and more preferably further contains a water-soluble acrylic resin (A2).
[0064] In some embodiments, the mass ratio (A1 / A2) of the aqueous acrylic emulsion (A1) to the water-soluble acrylic resin (A2) in the aqueous acrylic resin (A) is preferably 95 / 5 to 50 / 50, more preferably 90 / 10 to 60 / 40. In addition, in some embodiments, the mass ratio (A1 / A2) is preferably 90 / 10 to 30 / 70, more preferably 80 / 20 to 35 / 65, and particularly preferably 70 / 30 to 40 / 60.
[0065] When the mass ratio is within the above range, adhesion and abrasion resistance tend to be easily improved.
[0066] (Water-based urethane resin (B))
[0067] The aqueous urethane resin (B) is not limited as long as it is an aqueous resin containing a urethane bond, and is a general term for aqueous urethane emulsions (B1) and water-soluble urethane resins (B2). In addition, the aqueous urethane resin (B) is preferably an embodiment further containing a urea bond.
[0068] In the present invention, the aqueous urethane resin (B) includes a urethane acrylic resin containing both an acrylic resin part and a urethane resin part. In addition, an embodiment having a urea bond is also preferred.
[0069] As the water-based urethane resin (B), the following forms are preferred: the form of a urethane resin synthesized from polyols, polyhydroxy acids and polyisocyanates; the urethane urea resin as one embodiment of the water-based urethane resin is a form of a urethane resin in which a urethane prepolymer having an isocyanate group at the end synthesized from polyols, polyhydroxy acids and polyisocyanates is subjected to chain extension with polyamines. In the manufacture of the water-soluble urethane resin (B2), when the polyols and polyisocyanates are reacted, it is preferred to introduce acidic groups such as carboxyl groups and sulfone groups into the resin, neutralize them with alkaline compounds, and thereby solubilize them in water. From the viewpoint of water resistance, the acidic group is preferably a carboxyl group.
[0070] (Polyol)
[0071] As the above-mentioned polyol, it is not limited to the following, for example, polyester polyol, polyether polyol, polylactone polyol, polycarbonate polyol, polyolefin polyol, dimer alcohol, hydrogenated dimer alcohol, etc. can be preferably cited. These polyols can be used alone or in combination of two or more. The aqueous urethane resin preferably contains a structural unit consisting of at least one polyol selected from polyester polyol, polyether polyol and polycarbonate polyol. As the polyol, polyester polyol, polyether polyol and polycarbonate polyol are more preferred. The number average molecular weight of the polyol is preferably 500 to 5000.
[0072] (Polyether polyol)
[0073] As the above-mentioned polyether polyol, preferably polyethylene glycol, polypropylene glycol, polytrimethylene glycol, polytetramethylene glycol and copolymers thereof can be cited. The aqueous urethane resin preferably contains a structural unit consisting of a polyether polyol. In one embodiment, the aqueous urethane resin (B) preferably contains a structural unit derived from polyethylene glycol, and the aqueous urethane resin preferably contains 0.1 to 25% by mass of the structural unit derived from polyethylene glycol in the total mass, more preferably 2 to 15% by mass, and further preferably 2 to 10% by mass.
[0074] (Polyester polyol)
[0075] As the above-mentioned polyester polyol, it is preferred to have a form of a structural unit of a polyester polyol as a condensate of a dibasic acid and a diol containing a branched diol. As the dibasic acid, sebacic acid, adipic acid, succinic acid, etc. can be preferably used, and as the branched diol, it refers to a form in which at least one hydrogen on the carbon of the alkylene glycol has a substituent. Specifically, it is preferred to contain at least one selected from propylene glycol, 3-methyl-1,5-pentanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propylene glycol, and 2-methyl-1,3-propylene glycol in the total mass of the diol, and more preferably contain 60% by mass or more. In addition, the embodiment of the polyester polyol is not limited to these.
[0076] (Polycarbonate polyol)
[0077] The polycarbonate polyol is not limited to the production method or the type of diol constituting the polycarbonate polyol, and preferably includes a polycondensate produced by an ester exchange reaction between a diol consisting of an alkylene glycol and a carbonate compound. In addition, the polycarbonate polyol is preferably an alicyclic and / or aliphatic polycarbonate diol.
[0078] As the above-mentioned diol, for example, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,10-decanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butynediol, 2,2,4-trimethyl-1,3-pentanediol, 1,4-cyclohexanedimethanol, diethylene glycol, polypropylene glycol, dipropylene glycol, etc. are preferred, and these can be used alone or in combination of two or more. Polycarbonate polyols having a diol structure having other branched structures such as 3-methyl-1,5-pentanediol are preferred. The carbonate compound is not particularly limited, and dialkyl carbonate, diaryl carbonate or alkylene carbonate can be enumerated. As the specific example of the carbonate compound, dialkyl carbonates such as dimethyl carbonate, diethyl carbonate, dibutyl carbonate, diaryl carbonates such as diphenyl carbonate, alkylene carbonates such as ethylene carbonate can be enumerated.
[0079] (Polyisocyanate)
[0080] As the above-mentioned polyisocyanate, preferably aromatic diisocyanate, aliphatic diisocyanate, alicyclic diisocyanate, etc. can be mentioned. It should be noted that they can also be trimers to form isocyanurate ring structures. As aromatic diisocyanates, 1,5-naphthalene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dialkyl diphenylmethane diisocyanate, tetraalkyl diphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, toluene diisocyanate, etc. can be mentioned. As aliphatic diisocyanates, butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, etc. can be mentioned. As alicyclic diisocyanates, cyclohexane-1,4-diisocyanate, xylylene diisocyanate (xylylenediisocyanate), isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis (methyl isocyanate) cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, m-tetramethylxylene diisocyanate, hydrogenated 4,4-diphenylmethane diisocyanate, dimer diisocyanate formed by converting the carboxyl group of dimer acid into isocyanate group, etc. are mentioned. Among them, preferably at least one selected from toluene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, bis (methyl isocyanate) cyclohexane, hexamethylene diisocyanate, and trimers of hexamethylene diisocyanate. These polyisocyanates can be used alone or in combination of two or more.
[0081] (Polyhydroxy acid)
[0082] The polyhydroxy acid is not limited to the following, and a carboxyl-containing polyol can be used. For example, preferably, dimethylol alkanoic acids such as 2,2-dimethylol propionic acid, 2,2-dimethylol butyric acid, and 2,2-dimethylol valeric acid can be mentioned. They can be used alone or in combination of two or more. The polyhydroxy acid is used in the production process of water-based urethane resin, and its carboxyl group is introduced into the obtained urethane resin to have an acid value. The unreacted carboxyl group is neutralized and becomes water-based.
[0083] (Polyamine)
[0084] As compounds that can be used as the polyamines, there are various known amines, and preferred examples include 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, and dimer diamines obtained by converting carboxyl groups of dimer acids into amino groups. These can be used alone or in combination of two or more.
[0085] (Reaction terminator)
[0086] A reaction terminator may be used in combination with the above-mentioned polyamines. Examples of the reaction terminator include dialkylamines such as di-n-butylamine, amines having a hydroxyl group such as monoethanolamine, diethanolamine, 2-amino-2-methyl-1-propanol, tris(hydroxymethyl)aminomethane, 2-amino-2-ethyl-1-ethyl-1,3-propanediol, N-di-2-hydroxyethylethylenediamine, N-di-2-hydroxyethylpropylenediamine, and N-di-2-hydroxypropylethylenediamine, and monoamine-type amino acids such as glycine, alanine, glutamic acid, taurine, aspartic acid, aminobutyric acid, valine, aminocaproic acid, aminobenzoic acid, aminoisophthalic acid, and aminosulfonic acid.
[0087] (Neutralizer)
[0088] In order to make the aqueous urethane resin (B) water-based, it is preferred to neutralize the carboxyl groups in the resin with a basic compound.
[0089] (Basic Compounds)
[0090] As the alkaline compound, ammonia; organic amines such as monoethylamine, diethylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, triethanolamine, methyldiethanolamine, monoethanolamine, dimethylethanolamine, diethylethanolamine, morpholine, N-methylmorpholine, 2-amino-2-ethyl-1-propanol, and inorganic bases such as sodium hydroxide and potassium hydroxide can be used alone or in combination. However, in order to improve the water resistance of the film after drying, water-soluble and highly volatile substances that are easily dissociated by heat are preferred, and ammonia, trimethylamine, and triethylamine are particularly preferred. In addition, the acid value of the above-mentioned aqueous urethane resin (B) is preferably 5 to 100 mgKOH / g, and more preferably 10 to 60 mgKOH / g. These acid values are made aqueous by neutralization of the above-mentioned alkaline compounds.
[0091] When the aqueous urethane resin (B) is a urethane acrylic resin, the acrylic resin part and the urethane resin part may be an alternating copolymer, or a so-called graft polymer having a urethane resin part as the main chain and an acrylic resin part as the side chain, or having an acrylic resin part as the main chain and a urethane resin part as the side chain. The aqueous urethane emulsion resin (B1) may be a core / shell type having an acrylic resin part in the core part and a urethane resin part in the shell part, or may be a sea island structure having an acrylic resin part in the sea part and a urethane resin part in the island part.
[0092] The average particle size of the aqueous urethane emulsion (B1) is preferably in the range of 20 nm to 400 nm, more preferably in the range of 30 nm to 200 nm.
[0093] Specific examples of the aqueous urethane emulsion (B1) include Takelac W-5030, W-5661, W-6010, W-6020, W-6061, W-6355, W-605, WPB-341 (30), WS-4022 (manufactured by Mitsui Chemicals, Inc.), WEM-200U, WEM-3000, WEM-505C (manufactured by Taisei Fine Chemicals Co., Ltd.), AQUABRID 46777, 3756, UX-100, UX-110, AST531, AST49 (manufactured by Daicel Mika Co., Ltd.), and the like.
[0094] The aqueous urethane resin (B2) can be appropriately manufactured by a known method. For example, an acetone method using an inactive and hydrophilic organic solvent for isocyanate, a solvent-free synthesis method using no solvent at all, etc. can be cited. For example, the method described in Japanese Patent Publication No. 2013-234214 can be appropriately used.
[0095] (Water-based polyester resin (C))
[0096] The aqueous polyester resin (C) is preferably in the form of a polyester resin synthesized by a polycondensation reaction (esterification reaction) of a polyacid and / or its anhydride with a polyol. The reaction can be carried out under normal pressure or reduced pressure, and the molecular weight can be adjusted by the addition ratio of the polyacid and / or its anhydride to the polyol (excess ratio: equivalent ratio of hydroxyl groups to acid groups). As a method of water solubilization, it can be exemplified as follows: when the polyacid and / or its anhydride reacts with the polyol, water solubilization is carried out by introducing a carboxyl group of a copolymer of acrylic acid and methacrylic acid, or by introducing a sulfonic acid group of a metal salt such as sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid-5[4-sulfophenoxy]isophthalic acid, or these ester-forming derivatives. As metal salts, salts of Li, Na, K, Mg, Ca, Cu, Fe, etc. can be cited. Particularly preferred are 5-Sodium Sulfoisophthalate and Dimethyl-5-Sodium Sulfoisophthalate.
[0097] (polyacid and / or its anhydride)
[0098] As the polybasic acid and / or its anhydride that can be used in the synthesis of the aqueous polyester resin (C), a dibasic acid and / or its anhydride is preferably used, and specifically, there can be mentioned aromatic dibasic acids and their anhydrides such as terephthalic acid, isophthalic acid, and phthalic anhydride, alicyclic dibasic acids and their anhydrides such as tetrahydrophthalic anhydride, hexahydrophthalic anhydride, and 1,4-cyclohexanedicarboxylic acid, and aliphatic dibasic acids and their anhydrides such as succinic acid (anhydride), fumaric acid, maleic acid (anhydride), adipic acid, sebacic acid, azelaic acid, and humic acid, and their anhydrides. From these, it is possible to appropriately select and use them in consideration of the surface tension and surface free energy, softness, and adhesion of the resulting coating film.
[0099] (Polyol)
[0100] In addition, examples of the above-mentioned polyols include ethylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, trimethylolpropane, octanediol, 2-n-butyl-2-ethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, and 2-ethyl-1,3-hexanediol. An appropriate amount of polyol may be selected from these for use in consideration of the surface tension and surface free energy, flexibility, and adhesion of the resulting coating film.
[0101] The above-mentioned aqueous polyester resin (C) is preferably provided in the form of a solution dissolved in a solvent for the preparation of the aqueous primer composition of the present invention. As the solvent, a solvent that can dilute the polyester resin, water and / or a hydrophilic organic solvent can be preferably used. For example, alcohols such as methanol, ethanol, propanol, butanol, and glycol ethers such as ethylene glycol (mono, di) methyl ether, ethylene glycol (mono, di) ethyl ether, ethylene glycol monobutyl ether, diethylene glycol (mono, di) methyl ether, diethylene glycol (mono, di) ethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, triethylene glycol (mono, di) methyl ether, propylene glycol (mono, di) methyl ether, and dipropylene glycol (mono, di) methyl ether can be cited.
[0102] The acid value of the aqueous polyester resin (C) is preferably 80KOHmg / g or less, more preferably 60KOHmg / g or less, and further preferably 40KOHmg / g or less. By being in the above range, the hydrolysis of the polyester is suppressed, and the molecular weight can be maintained high, thereby improving the cohesive force of the coating film, and thus the wiping resistance becomes good. The acid value can be variously changed according to the types of the polyester polyol and tetracarboxylic dianhydride used, and therefore, those skilled in the art can easily select the types of polyester polyol and tetracarboxylic dianhydride to make it the above preferred range.
[0103] The weight average molecular weight of the aqueous polyester resin (C) is preferably about 3000 to 40000, more preferably 10000 to 30000. When the weight average molecular weight is 3000 or more, the scratch resistance of the coating film becomes good, and when the weight average molecular weight is 40000 or less, the fluidity becomes good and the printing suitability is improved.
[0104] Specific examples of the aqueous polyester resin (C) include PLAS COAT Z-446, Z-561, Z-565, Z-880, Z-3310, RZ-105, RZ-570, Z-730, and Z-760 (manufactured by Huying Chemical Industry Co., Ltd.), and ARON MELT PES-2155A30, 2255A30, 2500A30, 2655A30, 2405A30 and 2353A25 (manufactured by Toagosei Co., Ltd.).
[0105] The glass transition temperature (Tg) of the binder resin is preferably -20 to 100°C. This is because the scratch resistance and bending resistance are improved. It is more preferably -10 to 90°C, and further preferably 0 to 80°C. Here, the glass transition temperature (Tg) refers to a value measured based on JIS K0129. A measured value based on differential scanning calorimetry (DSC) can be used, and the measuring instrument can be DSC8231 manufactured by Rigaku Corporation.
[0106] <Extender Pigment>
[0107] The water-based primer composition of the present invention includes a body pigment. By including a body pigment, rheology can be adjusted to a viscosity range suitable for flexographic printing and gravure printing, and the surface tension of the water-based primer composition and the surface free energy of the primer layer formed by the water-based primer composition can be adjusted. As the body pigment used in the present invention, for example, silicon dioxide, calcium carbonate, barium sulfate, talcum, magnesium carbonate, barium carbonate, calcium sulfate, kaolin, mica, calcium silicate, aluminum silicate, etc. can be cited, wherein, from the viewpoint of rheological control such as viscosity, it is preferably selected from at least one of the group consisting of silicon dioxide, calcium carbonate, barium sulfate and talcum, particularly preferably silicon dioxide. This is because silicon dioxide has silanol groups on the surface, so the surface free energy is high, and the surface free energy of the primer layer itself improves. Body pigments can be used alone or in combination of two or more.
[0108] In the case of using silicon dioxide as a body pigment, the silicon dioxide (hydrophobic silicon dioxide) obtained by modifying and hydrophobizing the silanol groups on the silicon dioxide surface using an organosilicon compound can be used. The DBA (di-n-butylamine) value representing the hydrophobization degree of hydrophobic silicon dioxide is preferably 5 to 200, more preferably 20 to 175. By being in this range, the interaction with the dispersed resin is promoted, and the rheological adjustment is easy, and in addition, it is easy to adjust the surface tension. In addition, the lower the numerical value of the DBA value, the more it indicates that the silanol group is modified by the organosilicon compound, which means that the hydrophobization degree is higher.
[0109] The content of the above-mentioned body pigment in the water-based primer composition is preferably in the range of 1 to 15% by mass, more preferably 2 to 12% by mass, and further preferably 3 to 10% by mass. When it is more than 1% by mass, the gloss value can be reduced (matte feeling is given), and the surface free energy of the primer layer is improved. In addition, the body pigment is exposed on the surface, and the inking and leveling of the active energy ray-cured composition are made good by utilizing the concavoconvex. When it is below 15% by mass, the fluidity and the smoothness of the surface are improved, and the wiping resistance becomes good. In addition, if it is in the above-mentioned range, it is possible to take into account the transfer, inking, and leveling of the water-based primer composition on the paper substrate and / or the ink layer and the transfer, inking, and leveling of the active energy curing composition on the primer layer, so as to improve the substrate adhesion and interlayer adhesion of the laminate, and the wiping resistance becomes good.
[0110] The average particle size of the above-mentioned body pigment is preferably in the range of 1 to 10 μm, more preferably 2 to 8 μm, and further more preferably 2 to 5 μm. When the average particle size is 1 μm or more, the leveling property of the active energy ray-cured composition on the water-based primer is improved, and when it is below 10 μm, the scratch resistance is good, and a good matte feeling can be obtained. In addition, in order to adjust the flow characteristics and control the size of the surface unevenness, body pigments with different average particle sizes can also be used. It should be noted that the above-mentioned average particle size refers to the volume average particle size based on the laser diffraction method, and can be measured, for example, using T330EXII manufactured by Maiqikebaier Co., Ltd.
[0111] When silica is used as the extender pigment, the average particle size is preferably in the range of 1 to 10 μm, more preferably 2 to 8 μm, and even more preferably 2 to 5 μm.
[0112] The specific surface area m of the above extender pigment based on the BET method 2 / g is preferably 50 to 500 m 2 / g, more preferably 100 to 400 m 2 / g, more preferably 100 to 350 m 2 / g. At 50m 2 / g or above, the matte feeling is good, at 500m 2 When the content is not more than 50%, the fluidity of the primer composition can be maintained, so that the leveling becomes good.
[0113] When silica is used as the extender pigment, the specific surface area m based on the BET method is 2 / g is preferably 50 to 500 m 2 / g, more preferably 100 to 400 m 2 / g, more preferably 100 to 350 m 2 / g.
[0114] Specific examples of silica include Mizukasil P-705, P-707, P-709, P-78A, P-78D, P-78F, P-73, P-50 (manufactured by Mizusawa Chemical Industries, Ltd.), Nipsil E-74P, E75, E-743, E-150J, E-1030, E-200, E-170, E-220, E-200A, E-1009, E-220A, E-1011, N-300A, K-500, HD2, L-250, G-300 (manufactured by Tosoh Silica Co., Ltd.), SYLYSIA250, 250N, 256, 256N, 310P, 320, 350, 370, 380, 420, 430, 440, 450, 436, 446, 456, 530, 550, C-1504, C-1510, SYLOPHOBIC 100, 200, 702, 704, 4004, 507, 505, 603 (manufactured by Fuji SILYSIA Chemical Co., Ltd.), etc.
[0115] <Water-based solvents>
[0116] The water-based primer composition of the present invention comprises an aqueous solvent. As the aqueous solvent, water and / or a hydrophilic organic solvent are preferably used. In certain embodiments, the aqueous solvent preferably comprises 20 to 90% by weight, more preferably 25 to 85% by weight, and particularly preferably 30 to 80% by weight, relative to the gross weight of the aqueous primer composition. In addition, in certain embodiments, the aqueous solvent preferably comprises 30 to 85% by weight, more preferably 40 to 80% by weight, and particularly preferably 50 to 75% by weight, relative to the gross weight of the aqueous primer composition.
[0117] <Hydrophilic Organic Solvent>
[0118] The present invention preferably contains a hydrophilic organic solvent. There is no particular limitation on the hydrophilic organic solvent as long as it is soluble in water, and one type may be used alone or two or more types may be used in combination. A hydrophilic organic solvent refers to an organic solvent having a hydrophilic group such as an ether group or a hydroxyl group. The boiling point of the hydrophilic organic solvent is preferably 60 to 100°C, and more preferably 70 to 90°C. By including a hydrophilic organic solvent having a boiling point of 60°C or more, the surface tension is reduced, so that the leveling of the aqueous primer composition on the paper substrate and the ink layer is improved. When the boiling point is below 100°C, since there is almost no residual hydrophilic organic solvent in the coating film during the drying process, the surface free energy of the primer layer itself will not be reduced, so the inking and leveling of the active energy ray-cured composition are improved, thereby obtaining a good matte feel.
[0119] As the hydrophilic organic solvent, an alcohol organic solvent or an ether organic solvent is preferably used. As the alcohol organic solvent, methanol, ethanol, isopropanol, 2-butanol, diacetone alcohol, allyl alcohol, 2-methyl-2-propanol, etc. can be mentioned, and ethanol, methanol, isopropanol, 2-butanol are preferably used. As the ether organic solvent, n-propyl ether, ethylene glycol dimethyl ether, etc. can be mentioned, and n-propyl ether is preferably used.
[0120] The hydrophilic organic solvent preferably contains 1 to 15% by mass, more preferably 2 to 10% by mass, relative to the total mass of the aqueous primer composition. This is because the surface tension is reduced, so the leveling of the aqueous primer composition on the paper substrate and / or the ink layer is improved. In addition, the hydrophilic organic solvent has almost no residual solvent in the coating film after sufficient drying, so the surface free energy of the primer layer itself is not reduced, the ink adhesion and leveling of the active energy ray-curable composition are improved, and a good matte feeling can be obtained.
[0121] In some embodiments, the aqueous solvent preferably contains at least a hydrophilic organic solvent, and more preferably further contains water. When the aqueous solvent contains a hydrophilic organic solvent and water, the ratio of water to the total mass of the aqueous solvent is preferably 60 to 100 mass%, more preferably 70 to 100 mass%, and further preferably 80 to 100 mass%. There is no particular limitation on the hydrophilic organic solvent used in combination with water, but an alcoholic organic solvent can be preferably used.
[0122] In some embodiments, the aqueous primer composition contains a binder resin, a body pigment and a hydrophilic organic solvent, and preferably contains only water as the hydrophilic organic solvent. In this embodiment, the binder resin may include one or more than two of the resins described above. As a combination of resins in the binder resin, preferably include an aqueous acrylic emulsion (A1) and a water-soluble acrylic resin (A2). That is, in some embodiments, the aqueous primer composition includes an aqueous acrylic emulsion (A1) and a water-soluble acrylic resin (A2), a body pigment and a hydrophilic organic solvent, and the hydrophilic organic solvent preferably only includes water.
[0123] (Curing agent)
[0124] In the present invention, a polyisocyanate curing agent may be appropriately blended as needed within a range not hindering the purpose of the present invention.
[0125] (additive)
[0126] In the present invention, additives such as surface conditioners, leveling agents, wetting and penetrating agents, thickeners, anti-skinning agents, ultraviolet absorbers, antioxidants, crosslinking agents, preservatives, antifungal agents, viscosity regulators, and pH regulators may be appropriately blended as needed within the range not hindering the purpose of the present invention.
[0127] (Surface Conditioner)
[0128] In addition, in order to make the surface tension of the water-based primer composition of the present invention within the preferred range, a surface conditioner can be formulated within the range that does not hinder the purpose of the present invention. Specific examples of surface conditioners include anionic surface conditioners such as dialkyl sulfosuccinates, alkylnaphthalene sulfonates and fatty acid salts, nonionic surface conditioners such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl allyl ethers, acetylene glycols and polyoxyethylene-polyoxypropylene block copolymers, acetylene glycols, ethylene oxide addition type acetylene glycols, cationic surface conditioners such as alkylamine salts and quaternary ammonium salts, silicon-based surface conditioners and fluorine-based surface conditioners. Among them, nonionic surface conditioners such as acetylene glycols and ethylene oxide addition type acetylene glycols are preferred. It should be noted that the HLB (Hydrophile-Lipophile Balance) value of the surface conditioner is not particularly limited as long as the water-based primer composition has the desired surface tension, preferably 2 to 15, more preferably 3 to 10, and more preferably 4 to 9. The surface conditioner may be used alone or in combination of two or more.
[0129] In addition, the content of the surface conditioner contained in the water-based primer of the present invention is appropriately selected according to its purpose of use. Generally, it is preferably 0.01 to 10% by mass, and more preferably 0.5 to 8% by mass, relative to the total mass of the water-based primer composition. By adjusting the amount of the surface conditioner added as needed within the above range, the surface of the water-based primer composition can be adjusted.
[0130] (Leveling agent)
[0131] In the above-mentioned water-based primer layer, in order to adjust the surface characteristics (surface free energy, etc.) and improve the coating property, a leveling agent can be added, for example, a fluorine-based, acrylic-based, silicone-based and their adducts or mixtures and other known leveling agents can be used. The amount of the leveling agent can be appropriately determined according to the adjustment of the surface characteristics and the coating property.
[0132] (Viscosity of Primer Composition)
[0133] In the present invention, the viscosity of the aqueous primer composition is preferably 50 to 2500 mPa·s, more preferably 100 to 1500 mPa·s, and particularly preferably 800 to 1500 mPa·s. When the above-mentioned viscosity is 50 Pa·s or more, the transferability of the aqueous primer composition to the paper substrate becomes good, and when the above-mentioned viscosity is 2500 Pa·s or less, the leveling property after inking becomes good. In addition, the viscosity mentioned here is a measured value based on the method described in JIS K5600-2, for example, it can be measured using a cone-plate viscometer at a shear rate of 100 per second at 25°C, and the cone-plate viscometer uses a cone with a cone diameter of 35 mm and a cone angle of 1°.
[0134] In the present invention, in order to make the viscosity of the water-based primer into a preferred range, the content of the extender pigment in the water-based primer is preferably set to a range of 1 to 15 mass %, more preferably 2 to 10 mass %, and further preferably 3 to 8 mass %. The content of the hydrophilic organic solvent in the water-based primer is preferably 1 to 15 mass %, more preferably 2 to 10 mass %. The ratio of the binder resin in the water-based primer is 10 to 50 mass %, more preferably 20 to 40 mass %.
[0135] (Thickener)
[0136] In order to make the viscosity of the above-mentioned water-based primer composition a preferred range, a thickener can be contained within the scope of the effect of the present invention. By containing a thickener in the primer composition, it is possible to easily adjust the viscosity corresponding to the coating method. As such a thickener, carbamate thickeners and polyethylene oxide thickeners can be enumerated. As a specific example of a carbamate thickener, ADEKA Nol UH-756VF, UH-752, UH-472, DISPARLON AQ-580, AQ-600, AQ-607, BYK-420, etc., made by ADEKA, can be enumerated. As a specific example of a polyethylene oxide thickener, PEO-1, PEO-2, PEO-3, POLYOX N-80, N-750, etc., made by Sumitomo Seika, can be enumerated. These may be used alone or in combination of two or more.
[0137] In the total mass of the water-based primer composition, the content of the thickener is preferably 0.1 to 10.0 mass %, more preferably 0.3 to 8.0 mass %, and particularly preferably 0.5 to 5.0 mass %. If the content of the thickener is more than 0.1 mass %, the viscosity of the primer composition will not become too low, the body pigment in the system is not easy to settle, and the storage stability is improved. In addition, if the content of the thickener is less than 10.0 mass %, the viscosity of the primer composition will not become too high, and it is not easy to produce uneven thickness caused by uneven coating and poor leveling. It should be noted that, when using a water-soluble thickener, the content of the thickener refers to the solid component conversion content in the thickener.
[0138] <Manufacturing of water-based primer>
[0139] The method for producing the water-based primer of the present invention includes mixing necessary amounts of a binder resin, an extender pigment, an aqueous solvent, and, if necessary, a pigment, a curing agent, and additives, and stirring them thoroughly with a stirrer or the like, or dispersing them using a sand mill or the like.
[0140] <Active Energy Ray Curable Layer>
[0141] In the laminate for packaging materials of the present invention, the active energy ray-curable layer is formed by a cured product of an active energy ray-curable composition. Specifically, the active energy ray-curable composition is printed on the primer layer and the obtained printed layer is irradiated with active energy rays to cure the composition constituting the printed layer. The 60° specular gloss of the active energy ray-curable layer is preferably 40 or less, and the matte property is excellent. It is more preferably 18 or less, and further preferably 11 or less. The gloss value is measured using micro-TRI-gloss at an incident angle of 60°.
[0142] <Active Energy Ray-Curable Composition>
[0143] The active energy ray composition of the present invention is not particularly limited as long as it contains a compound that is cured by active energy rays, but preferably contains resin particles from the viewpoint of abrasion resistance and matting properties. In addition, as a preferred composition of the active energy ray curable composition, a composition containing a multifunctional urethane acrylate, a monofunctional ethylenically unsaturated monomer, a bifunctional ethylenically unsaturated monomer, resin particles and a photopolymerization initiator can be exemplified.
[0144] <Manufacturing of Active Energy Ray-Curable Composition>
[0145] As a method for producing an active energy ray-curable composition, a polyfunctional urethane acrylate, a monofunctional ethylenically unsaturated monomer, a difunctional ethylenically unsaturated monomer, resin particles and a photopolymerization initiator can be produced by stirring for about 30 minutes to 3 hours using a stirrer (disperser) with a paddle. It should be noted that in the case where mixing is difficult or the viscosity and the like are prone to becoming uneven, a roll mill, a ball mill, a pebble mill, a grinder, a sand mill, etc. can be used.
[0146] <Resin particles>
[0147] In the present invention, the resin particles assume the functions of friction resistance and matte. As the resin particles, the average particle size is preferably 1 to 10 μm, more preferably 1.5 to 8 μm, further preferably 2 to 6 μm, and particularly preferably 2 to 3 μm. The average particle size here refers to the volume average particle size based on the laser diffraction method, for example, it can be measured using T330EXII manufactured by Maiqikebaier Co., Ltd. In the total mass of the active energy ray-curable composition, the resin particles preferably contain 5 to 40% by mass, more preferably 10 to 35% by mass, and further preferably 20 to 30% by mass.
[0148] As preferred specific examples of resin particles, for example, carbamate resin particles, silicone resin particles, melamine resin particles, melamine-benzoguanamine resin particles, acrylic resin particles (for example, polymethyl methacrylate resin particles), acrylic-styrene copolymer resin particles, polycarbonate resin particles, polyethylene resin particles, polystyrene resin particles, benzoguanamine resin particles, etc. can be cited. They can be used alone or in combination of two or more. Among them, carbamate resin particles are more preferred. The above-mentioned resin particles can be used in combination of two or more as needed.
[0149] Specific examples of the urethane resin fine particles include cross-linked urethane beads such as ART PEARL C-1000 transparent, ART PEARL C-600 transparent, ART PEARL C-400 transparent, ART PEARL C-800, ART PEARL MM-120T, ART PEARL JB-800T, ART PEARL JB-600T, ART PEARL P-800T, and ART PEARL P-400T (manufactured by Negami Industries, Ltd.).
[0150] Specific examples of the silicone resin fine particles include KMP-594, KMP-597, KMP-598, KMP-600, KMP-601, KMP-602 (manufactured by Shin-Etsu Chemical Co., Ltd.), TREFIL E-506S, and EP-9215 (manufactured by Dow Corning Toray Corporation).
[0151] Specific examples of melamine resin fine particles include EPOSTAR SS, EPOSTAR S, EPOSTAR FS, EPOSTAR S6, and EPOSTAR S12 (manufactured by Nippon Shokubai Co., Ltd.). Specific examples of melamine-benzoguanamine resin fine particles include EPOSTAR M30 (manufactured by Nippon Shokubai Co., Ltd.).
[0152] Specific examples of acrylic resin fine particles include EPOSTAR MA1002, EPOSTAR MA1004, EPOSTAR MA1006, EPOSTAR MA1010 (manufactured by Nippon Shokubai Co., Ltd.), TAFTIC FH-S005, TAFTIC FH-S008, TAFTIC FH-S010, TAFTIC FH-S015, TAFTIC FH-S020 (manufactured by Toyobo Co., Ltd.), Chemisnow MX-80H3wT, MX-150, MX-180TA, MX-300, MX-500, MX-1000, MX-1500H, MX-2000, MX-3000 (manufactured by Soken Chemical Co., Ltd.), and the like.
[0153] Specific examples of acrylic-styrene copolymer resin fine particles include EPOSTAR MA2003 (manufactured by Nippon Shokubai Co., Ltd.), FS-102, FS-201, FS-301, MG-451, and MG-351 (manufactured by Nippon Paint Industrial Coatings Co., Ltd.).
[0154] Specific examples of polycarbonate resin fine particles include fine particles described in Japanese Patent Application Laid-Open No. 2014-125495, fine particles obtained by the production method described in Japanese Patent Application Laid-Open No. 2011-26471, and fine particles obtained by the method described in Japanese Patent Application Laid-Open No. 2001-213970.
[0155] Specific examples of polyethylene resin fine particles include MIPELON XM-220 and XM221U (manufactured by Mitsui Chemicals, Inc.) and FLO-BEADS LE-1080 (manufactured by Sumitomo Seika Chemicals, Ltd.).
[0156] Specific examples of the polystyrene-based fine particles include Chemisnow SX-130H, SX-350H, and SX-500H (manufactured by Soken Chemical Co., Ltd.).
[0157] Specific examples of the benzoguanamine resin fine particles include EPOSTAR MS, EPOSTAR M05, and EPOSTAR L15 (manufactured by Nippon Shokubai Co., Ltd.).
[0158] <Paper base material>
[0159] The paper substrate used in the present invention is not particularly limited, and is preferably a common paper, corrugated paper, etc. The film thickness is not particularly specified, and a paper substrate of 0.2 mm to 1.0 mm can be preferably used, and the printed surface can also be subjected to a corona treatment. In addition, in order to impart designability, the paper substrate can be subjected to a vapor deposition treatment on the surface with a metal such as aluminum, and a surface treatment such as a corona treatment can also be further applied. For example, coated thick paper, Marie-coated paper, etc. can be preferably cited.
[0160] <Printing ink composition>
[0161] The above-mentioned printing ink composition can include, for example, known offset ink compositions, ultraviolet curable offset inks, gravure ink compositions, flexographic ink compositions, ultraviolet curable flexographic ink compositions, and other ink compositions, and can be any printing ink composition. Among them, offset ink compositions and ultraviolet curable offset inks are preferred because they have a wide color gamut and are easy to increase in printing concentration, so that a printing ink layer with high color reproducibility and design properties can be formed. The printing ink composition can be an organic solvent-based, solvent-free, or aqueous.
[0162] <Printing of Printing Ink Layer>
[0163] As a printing method for the printing ink composition, a known method can be used. For example, offset printing, flexographic printing, gravure printing, screen printing, etc. can be mentioned, and offset printing is preferred. The thickness of the ink layer is preferably 0.1 to 15 μm, and more preferably 0.5 to 12 μm. In addition, the above-mentioned printing ink composition can be combined to form an ink layer, and the printing layer can also be formed by drying or ultraviolet curing after printing.
[0164] <Printing of water-based primer layer>
[0165] In the present invention, it is preferred to form a primer layer using the water-based primer of the present invention on a substrate by printing. As a printing method for printing the water-based primer on a substrate, a known method can be used, and flexographic printing and gravure printing are preferred.
[0166] <Manufacturing of Laminated Body>
[0167] The method for producing the laminate of the present invention may be exemplified by a method in which a primer layer is formed on a paper substrate by flexographic printing or gravure printing, an active energy ray curing composition is printed on the primer layer, and then the active energy ray is irradiated to form the active energy ray curing layer. In addition, the following method may be exemplified: after a printed layer formed of a printing ink composition is formed on a paper substrate by a known printing method, a primer layer is formed from an aqueous primer composition by flexographic printing or gravure printing, an active energy ray curing composition is printed on the primer layer, and then the active energy ray is irradiated to form the active energy ray curing layer.
[0168] The method for printing or applying the active energy ray-curable composition is not particularly limited, and examples thereof include wet coating methods such as spraying, showering, dipping, flow coating, gravure printing, flexographic printing, roll coating, spin coating, dispenser, inkjet printing, and screen printing. Among them, gravure printing and flexographic printing are preferred.
[0169] As active energy rays, for example, ultraviolet rays such as far ultraviolet rays, ultraviolet rays, and near ultraviolet rays can be cited. On the other hand, electron rays and proton rays can also be used. In this case, curing can be achieved even without using a photopolymerization initiator, but from the perspective of curing speed, ease of obtaining an irradiation device, price, etc., the effect based on ultraviolet irradiation is preferred.
[0170] As a method of curing by ultraviolet irradiation, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a carbon arc lamp, a metal halide lamp, a xenon lamp, a chemical lamp, an electrodeless discharge lamp, an LED, etc., which emit light in the wavelength region of 150 to 450 nm, is used, and the accumulated light intensity is 30 to 5000 mJ / cm 2 , preferably 100 to 1000 mJ / cm 2 After ultraviolet irradiation, heating may be performed as required to achieve complete curing.
[0171] Example
[0172] Hereinafter, the present invention will be specifically described as examples, but the present invention is not limited to the following examples. In the present invention, "parts" means "parts by mass" and "%" means "% by mass" unless otherwise specified.
[0173] (Surface tension)
[0174] The surface tension refers to the surface tension based on the Wilhelmy method, and is measured, for example, using a high-precision surface tension meter DY-700 (manufactured by Kyowa Interface Chemical Co., Ltd.) The liquid temperature during the measurement was set to 25°C.
[0175] (Surface free energy)
[0176] The surface free energy was measured using a fully automatic contact angle meter DM-701 manufactured by Kyowa Interface Science Co., Ltd. It is a value calculated by the Kaelble-Uy method using the contact angles of water and n-hexadecane obtained by dropping 1 μL of water (pure water) on the surface of the primer layer and measuring the contact angle after 30 seconds, and then dropping 1 μL of n-hexadecane on the surface of the primer layer and measuring after 30 seconds.
[0177] (Average particle size)
[0178] The average particle size refers to a volume average particle size obtained by a laser diffraction method, and is measured using T330EXII manufactured by Microtrac Biore Corporation.
[0179] (Viscosity)
[0180] The viscosity is a measured value according to the method described in JIS K5600-2, and is measured at a shear rate of 100 per second under a 25° C. environment using a cone-plate viscometer having a cone diameter of 35 mm and a cone angle of 1°.
[0181] (Glass transition temperature)
[0182] The glass transition temperature (Tg) was determined by the method described in JIS K0129. Specifically, it was determined by DSC (differential scanning calorimetry). It should be noted that the measuring instrument used was Rigaku DSC8231, and the measuring temperature range was -70 to 150°C, the heating rate was 10°C / min, and the midpoint between the endothermic start temperature and the end temperature of the glass transition in the DSC curve was taken as the glass transition temperature.
[0183] (Manufacturing Example 1: Preparation of Active Energy Ray Curable Composition U1)
[0184] 12 parts of urethane acrylate (BEAMSET 550B, manufactured by Arakawa Chemical Industries, Ltd.), 47 parts of 4-HBA (4-hydroxybutyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 25 parts of ART PEARL MM120T (urethane fine particles, average particle size 2 μm, glass transition temperature (Tg) 22° C., manufactured by Negami Industries), 4 parts of Omnirad TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide, manufactured by IGM) as a photopolymerization initiator, and 12 parts of a silicone-based defoaming agent as an additive were mixed and stirred for 90 minutes using a stirrer with a paddle to obtain an active energy ray-curable composition U1.
[0185] (Manufacturing Example 2: Preparation of Active Energy Ray Curable Composition U2)
[0186] 10 parts of urethane acrylate (BEAMSET 550B, manufactured by Arakawa Chemical Industries, Ltd.), 39 parts of 4-HBA (4-hydroxybutyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 35 parts of ART PEARL MM120T (urethane-based fine particles, average particle size 2 μm, glass transition temperature (Tg) 22° C., manufactured by Negami Industries), 4 parts of Omnirad TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide, manufactured by IGM) as a photopolymerization initiator, and 12 parts of a silicone-based defoaming agent as an additive were mixed and stirred for 90 minutes using a stirrer with a paddle to obtain an active energy ray-curable composition U2.
[0187] (Manufacturing Example 3: Preparation of Active Energy Ray Curable Composition U3)
[0188] 21 parts of urethane acrylate (BEAMSET 550B, manufactured by Arakawa Chemical Industries, Ltd.), 57 parts of 4-HBA (4-hydroxybutyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 6 parts of ART PEARL MM120T (urethane-based fine particles, average particle size 2 μm, glass transition temperature (Tg) 22° C., manufactured by Negami Industries), 4 parts of Omnirad TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide, manufactured by IGM) as a photopolymerization initiator, and 12 parts of a silicone-based defoaming agent as an additive were mixed and stirred for 90 minutes using a stirrer with a paddle to obtain an active energy ray-curable composition U3.
[0189] (Example 1: Preparation of water-based primer composition S1)
[0190] 80 parts of an aqueous acrylic emulsion (A1) (styrene-acrylic emulsion 1, Tg 25°C, solid content 40%), 5 parts of silica-1 (average particle size 3 μm, oil absorption 260 ml / 100 g), 5 parts of ethanol, 8 parts of water, 2 parts of a dispersant (BYK193) as an additive, and 2 parts of a surface conditioner (TEGO Foamex 810, silicone-based) were mixed and stirred for 20 minutes using a stirrer with a paddle to obtain an aqueous primer composition S1.
[0191] (Examples 2 to 21, Comparative Examples 1 to 2: Preparation of Water-Based Primer Compositions S2 to S21, T1 to T2)
[0192] Water-based primers S2 to S21 and T1 to T2 were obtained in the same manner as in Example 1 except that the raw materials and formulations described in Tables 1 and 2 were changed. In the tables, numerical values without unit symbols represent parts, and blank columns represent no formulation.
[0193] In addition, the abbreviations in the table indicate the following, and the solvent of the binder resin is water.
[0194] Water-soluble acrylic resin (A2): Tg 19°C, solid content 25%;
[0195] Water-based urethane resin (B1): Tg 25°C, solid content 30%;
[0196] Polyester resin (C): Tg 20°C, solid content 25%;
[0197] Styrene-butadiene resin: Tg26℃, solid content 43%;
[0198] Silica-2: average particle size 0.5 μm;
[0199] Silica-3: average particle size 6μm, oil absorption 250ml / 100g;
[0200] Silica-4: average particle size 12 μm, oil absorption 240 ml / 100 g;
[0201] Silica-5: average particle size 3.9 μm, oil absorption 230 ml / 100 g, DBA value 50;
[0202] Calcium carbonate: average particle size 3μm, oil absorption 20ml / 100g;
[0203] Sedimentary barium sulfate: average particle size 3μm;
[0204] Clay: average particle size 3μm, oil absorption 51ml / 100g;
[0205] Methanol: boiling point 64.7°C;
[0206] Isopropyl alcohol: boiling point 82.3°C;
[0207] 2-Butanol: boiling point 100°C.
[0208] [Table 1]
[0209]
[0210] [Table 2]
[0211]
[0212] (Example 22: Preparation of laminate T1)
[0213] First, on AURORACOAT (high gloss coated paper, paper thickness 81 μm, manufactured by Nippon Paper Industries) as a paper substrate, "FD CARTON X ink M (manufactured by Toyo Ink Co., Ltd., containing a trifunctional or higher multifunctional (meth) acrylic monomer)" as a UV curable offset ink was printed at an ink concentration of 1.75 (measurement device: X-Rite eXact (manufactured by X-Rite Inc.), conditions: illumination D50, standard observer 2°, concentration state E, no filter) on the upper half of the paper substrate in the printing direction, and cured with a UV lamp. In this way, a printed matter having only a paper substrate without an ink layer and a portion having an ink layer can be produced. It should be noted that the printing speed of the above printing is 8,000 sheets / hour, the types of UV lamps are 2 air-cooled metal halide lamps and 1 high-pressure mercury lamp, and the intensity of the UV lamp is set to a total of 160 W / cm (cumulative light amount 450 mJ / cm 2 ). Then, the water-based primer S1 of Example 1 was applied to the printed matter of the FD CARTON X ink M obtained above using the flexographic coating unit of the sheet-fed printing press "LITHRONE 26 (manufactured by Komori Corporation)", and dried using a far infrared ray and hot air dryer. The anilox roller of the coating unit had a triple spiral engraving pattern, 80 lines / inch, and a unit volume of 15 ml / m 2 Then, the active energy ray curing composition U1 obtained in Manufacturing Example 1 was applied to the printed matter obtained above using a flexographic coating unit of a sheet-fed printing press "LITHRONE 26 (manufactured by Komori Corporation)" in the same manner as the aqueous primer composition, and cured using a UV lamp to obtain a laminate T1. It should be noted that the anilox roller used as the coating unit had an engraved pattern of three spirals, a line number of 90 lines / inch, and a unit volume of 25 ml / m 2 In the case of flexographic coating, the temperature was controlled so that the printing speed was 8000 sheets / hour and the liquid temperature of S1 was 25° C. The type, number and intensity of the UV lamp were the same as those of the curing conditions of the FD CARTON X ink M described above.
[0214] (Examples 23 to 44, Comparative Examples 3 to 4: Preparation of Laminated Bodies L2 to L23, M1 to 2)
[0215] By the same method as Example 22, under the composition conditions shown in Tables 3 and 4, using the water-based primers S2 to S21 obtained in Examples 2 to 21 and the active energy ray-curing compositions U2 and U3 obtained in Preparation Examples 2 and 3, laminates L2 to L23 and M1 to 2 are obtained.
[0216] [Table 3]
[0217]
[0218] [Table 4]
[0219]
[0220] (evaluate)
[0221] The following evaluations were performed using the laminate for packaging materials having the aqueous primer composition and the active energy ray-curable composition obtained in the above Examples and Comparative Examples in this order. The evaluation results are shown in Tables 3 and 4.
[0222] <Stain resistance>
[0223] For the laminates obtained in the examples and comparative examples, the gloss values of the water-based primer / active energy ray-cured layer on the ink layer of FD CARTON X ink M and the water-based primer / active energy ray-cured layer directly laminated on the paper substrate without printing the ink layer of FD CARTON X ink M were randomly measured at 50 locations, and the relative standard deviation of the gloss value (the ratio of the deviation relative to the average value of the gloss value) was evaluated. The larger the relative standard deviation, the higher the gloss unevenness, which is considered as a deterioration in the printed appearance (color spots). The gloss value was measured using micro-TRI-gloss manufactured by BYK at an incident angle of 60°. The evaluation criteria are as follows.
[0224] 5 (excellent): less than 2%
[0225] 4 (good): 2% or more and less than 3%
[0226] 3 (allowable): 3% or more and less than 5%
[0227] 2 (Not acceptable): 5% or more and less than 10%
[0228] 1 (poor): more than 10%
[0229] In addition, the practically usable evaluations are 3, 4, and 5.
[0230] <Matting properties>
[0231] For the laminates obtained in the examples and comparative examples, the gloss value of the water-based primer / active energy ray-cured layer directly laminated on the paper substrate without printing the ink layer of FD CARTON X ink M was measured. The gloss value was measured using micro-TRI-gloss manufactured by BYK at an incident angle of 60°. The evaluation criteria are as follows.
[0232] 5 (excellent): 11 or less
[0233] 4 (good): gloss value greater than 11 and less than 18
[0234] 3 (OK: gloss value greater than 18 and less than 40
[0235] 2 (Not acceptable): Gloss value greater than 40 and less than 50
[0236] 1 (bad): gloss value greater than 50
[0237] In addition, the practically usable evaluations are 3, 4, and 5.
[0238] <Wipe resistance>
[0239] The laminates obtained in the examples and comparative examples were placed in a Sutherland Type Ink Rub Tester (manufactured by Toyo Seiki Seisakusho) in such a manner that the cured layers of the water-based primer / active energy ray-cured layer on the ink layer of FD CARTON X Ink M were in contact with each other, and after applying a load of 2 pounds and reciprocating a predetermined number of times, the abrasion resistance was evaluated by visually confirming whether the cured layer was peeled off and the substrate was visible. The evaluation criteria are as follows.
[0240] 5 (excellent): The cured layer did not peel off even after 10,000 reciprocations, and the base was not visible.
[0241] 4 (good): After 10,000 reciprocations, the cured layer peeled off and the base was seen, but after 9,000 reciprocations, the base was no longer seen.
[0242] 3 (acceptable): After 9000 reciprocations, the cured layer peeled off and the base was seen, but after 8000 reciprocations, the base was not seen.
[0243] 2 (unacceptable): The cured layer peeled off and the base was seen after 8000 reciprocations, but the base was not seen after 7000 reciprocations.
[0244] 1 (poor): Even after 7000 reciprocations, the cured layer peeled off and the base was seen.
[0245] In addition, the practically usable evaluations are 3, 4, and 5.
[0246] As can be seen from Tables 3 and 4, according to the present invention, it is possible to provide an aqueous primer composition having excellent color spot resistance (resistance to gloss unevenness) when an active energy ray-curable composition is applied on a primer layer, and a laminate for packaging materials having excellent cosmetic appearance (matte properties) and scratch resistance.
[0247] Comparative Examples 1 and 2, which do not contain an extender pigment, are inferior in color spot resistance and matte properties.
Claims
1. A water-based primer composition for forming the primer layer of a laminate for packaging materials having a paper substrate, a primer layer and an active energy ray-curable layer in this order, the water-based primer composition comprising a binder resin, an extender pigment and an aqueous solvent.
2. The water-based primer composition according to claim 1, wherein the surface tension thereof is 24 to 38 mN / m.
3. The water-based primer composition according to claim 1 or 2, wherein: The surface free energy of the primer layer is 24 to 40 dyne / cm.
4. The water-based primer composition according to claim 1 or 2, wherein: The aqueous solvent includes a hydrophilic organic solvent.
5. The water-based primer composition according to claim 1 or 2, wherein: The viscosity of the water-based primer composition is 50 to 2500 mPa·s.
6. The water-based primer composition according to claim 1 or 2, wherein: The binder resin includes at least one selected from the group consisting of an aqueous acrylic resin (A), an aqueous urethane resin (B), and an aqueous polyester resin (C).
7. The water-based primer composition according to claim 1 or 2, wherein: The extender pigment includes at least one selected from the group consisting of silicon dioxide, calcium carbonate, barium sulfate, and talc.
8. The water-based primer composition according to claim 1 or 2, wherein: The average particle size of the extender pigment is 1 to 10 μm.
9. The water-based primer composition according to claim 4, wherein The boiling point of the hydrophilic organic solvent is 70-90°C.
10. The aqueous primer composition according to claim 1 or 2, which is used for flexographic printing or gravure printing. 11 . A laminate for packaging materials, comprising a paper substrate, a primer layer formed from the aqueous primer composition according to claim 1 , and an active energy ray-curable layer in this order, wherein the active energy ray-curable layer contains resin fine particles. 12 . The laminate for packaging materials according to claim 11 , further comprising an offset printing layer.
13. The packaging material laminate according to claim 11, wherein The active energy ray-cured layer has a 60° specular glossiness of 40 or less.
14. A method for producing a laminate for packaging materials, which is a method for producing a laminate for packaging materials having a paper substrate, a primer layer and an active energy ray-curable layer in this order, comprising: A step of forming the primer layer on a paper substrate by flexographic printing or gravure printing of an aqueous primer composition comprising a binder resin, an extender pigment and an aqueous solvent; as well as A step of printing an active energy ray-curable composition on the primer layer and then irradiating the primer layer with active energy rays to form a cured layer of the active energy ray-curable composition.
Citation Information
Patent Citations
Method and apparatus for producing fine sphericl particle dispersion and fine spherical particle
JP2001213970A
Coated paper
JP2005089932A
Activating energy beam-curing type overprint varnish composition and use of the same
JP2007045962A
Continuous production method for polycarbonate granules
JP2011026471A
Aqueous polyurethane resin and use of the same
JP2013234214A